Development of Abaqus WCM plugin for progressive failure analysis of type IV composite pressure vessels based on Puck failure criterion. (January 2022) - Ahmadi Jebeli, Mohsen; Heidari-Rarani, Mohammad
Highlights: Progressive failure analysis is performed based on Puck failure criterion. Debonding of liner/composite due to curing is studied using CZM. Variation of thickness and winding angle is precisely simulated in domes. WCM plugin is developed for progressive failure analysis of type IV CPVs. Abstract: The type IV composite pressure vessels (CPVs) are used as a reliable solution for storing compressed gas but still require research and development to reach commercial advancements. The main two challenges in the design of CPVs are: a) debonding of liner and composite shell during the curing process, and b) accurate finite element modeling of the thickness and angle variation of helical layers at the dome regions. In this study, debonding of composite shell from polymeric liner and bosses due to the temperature variations during the curing process is simulated by using bilinear cohesive law. Regarding the second challenge, the Abaqus WCM plugin is used to model the actual geometry of two-liter type IV CPV's domes by defining and controlling manufacturing parameters. The UVARM subroutine is developed to apply stress analysis and predict the damage initiation using the Maximum Stress, Tsai-Wu, Tsai-Hill, Hashin, and Puck failure criteria. Also, a USDFLD subroutine is written to implement progressive failure analysis using the Puck failure criterion with sudden material degradation model. The numerical axial and radial displacements as well as burst pressure results are compared with the experimental results available in the literature. A good correlation is observed between the finite element and experimental results. Also, numerical results showed that the initial debonding gap due to curing does not affect the progressive damage of the composite shell.